2021
DOI: 10.1177/24741264211028519
|View full text |Cite
|
Sign up to set email alerts
|

Board Certification Is Associated With a Reduced Risk of Endophthalmitis After Intravitreal Injections

Abstract: Purpose: This work investigates associations between physician qualifications and the risk of postintravitreal injection endophthalmitis. Methods: This retrospective analysis of data from medical claims studied Medicare beneficiaries undergoing 1 or more intravitreal injections between January 1, 2013, and December 31, 2017. Logistic regression analysis was performed to assess whether board certification status or retina subspecialty training was associated with lower risk of postinjection endophthalmitis, con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
(38 reference statements)
0
2
0
Order By: Relevance
“…Although some studies have demonstrated the benefits of utilizing physician extenders to perform some of the most common procedures in ophthalmology, another study demonstrated that there was a 28% reduced odds of endophthalmitis when American Board of Ophthalmology (ABO) board-certified providers administered intravitreal injections [11 ▪ ]. Despite the rates of endophthalmitis being low, this study should raise concern for allowing NPPs to administer intravitreal injections.…”
Section: Rigorous Training Program and Supervisionmentioning
confidence: 76%
See 1 more Smart Citation
“…Although some studies have demonstrated the benefits of utilizing physician extenders to perform some of the most common procedures in ophthalmology, another study demonstrated that there was a 28% reduced odds of endophthalmitis when American Board of Ophthalmology (ABO) board-certified providers administered intravitreal injections [11 ▪ ]. Despite the rates of endophthalmitis being low, this study should raise concern for allowing NPPs to administer intravitreal injections.…”
Section: Rigorous Training Program and Supervisionmentioning
confidence: 76%
“…The involvement of physician extenders in this capacity may serve to undermine the boundary between ophthalmologists and nonophthalmologists and could ultimately lead to patient harm if less-trained providers begin to do procedures without adequate background and/or supervision. This is particularly dangerous for invasive procedures such as intravitreal injections where evidence suggests that noncertified proceduralists have worse outcomes [11 ▪ ].…”
Section: Scope Of Practicementioning
confidence: 99%